Perlindungan Hukum terhadap Anak Korban Eksploitasi Fisik, Sosial dan Seksual - Ayu Winda Amelia (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
The system that aims to protect the rights and welfare of children including the protection of minors. Children under age are often exposed to various types of violence, exploitation and discrimination. Therefore, various rules and regulations have been made to provide comprehensive protection. Law number 35 of 2014 concerning amendments to Law number 23 of 2002 concerning child protection regulates child protection in Indonesia. This law shows how important it is to protect children's rights, including the right to live, develop and be protected from violence. In addition, to deal with the problems faced by children, prevention and rehabilitation efforts are also very important. The game violates the law on child protection requires cooperation between the government, society, and non-governmental organizations. It is hoped that children can grow and develop in a safe and secure environment with strict supervision and law enforcement.